Bahasa Inggris - Ni Komang Evi Octiyana; Ni Desak Made Santi Diwyarthi (JURNAL KEPARIWISATAAN, 2023)
This study aimed to investigate the impact of job insecurity, workload, and employee work stress due to the effect of the COVID-19 pandemic. The study involved 116 employees of Hotel I.B.S.B., and data were collected using questionnaires, observations, interviews, and literature studies. The method was a multiple regression analysis method. The findings of this study revealed that both job insecurity and workload have a significant and positive impact on employee work stress. This indicates that as job insecurity and workload increase, the work stress experienced by Hotel IBSB employees also rises. The combined effect of job insecurity and workload on work stress accounted for 57.2% of the variation. To address these issues, the hotel management should focus on fostering a comfortable work environment with effective communication to alleviate uncertainties and concerns related to work. Providing workloads that align with each employee's capabilities, assessing stress-causing factors, and implementing preventive measures are crucial to mitigating employee work stress.